2016
DOI: 10.1515/pjfns-2015-0037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microbial Transglutaminase on Ice Cream Heat Resistance Properties – a Short Report

Abstract: The objective of this study was to investigate the effect of the addition of transglutaminase (TG) preparation Saprovia L ® (PMT TRADING Co. Ltd, Lodz, Poland) on the properties of ice cream with 40 g/kg and 70 g/kg fat content. TG was added at a concentration of 2 U/g protein. We studied the effect of transglutaminase on fresh and 3-month-stored at -25ºC ice cream. Ice cream mixes were prepared with 5 g/kg stabilizer. Melting test was performed after thermal shocks until the "1st drop" occurrence. The amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
2
0
2
Order By: Relevance
“…Трансглютаминаза TG (EC2.3.2.13) -фермент, признанный безопасным (GRAS -Generally Recognized As Safe) и используемый в пищевой промышленности. Он изменяет функциональные свойства молочных белков, способствует образованию структуры при использовании различных белков, соединяя их, в частности белков сои, молочных, глютена и других белки [63,64].…”
Section: использование трансглютаминазы в мороженомunclassified
See 1 more Smart Citation
“…Трансглютаминаза TG (EC2.3.2.13) -фермент, признанный безопасным (GRAS -Generally Recognized As Safe) и используемый в пищевой промышленности. Он изменяет функциональные свойства молочных белков, способствует образованию структуры при использовании различных белков, соединяя их, в частности белков сои, молочных, глютена и других белки [63,64].…”
Section: использование трансглютаминазы в мороженомunclassified
“…Исследование [64] также посвящено изучению свойств трансглютаминазы в мороженом. Авторами работ отмечено, что применение трансглютаминазы положительно сказывается на стабильности образцов к повторным тепловым шокам.…”
Section: использование трансглютаминазы в мороженомunclassified
“…TG treatment of milk proteins modifies their functional properties such as solubility and hydration ability, rheological and emul-sifying properties and improve protein heat stability. It has been suggested that various dairy products like yoghurt with reduced fat and protein could be produced by TG having the texture similar to the full fat and high total solid products (Faergemand et al, 1999;Kasprzyk et al, 2016;Romeih and Walker, 2017). In other words, the action of TG could simulate fat in fermented milk products and could replace fat substitutes in low-fat products (Lorenzen et al, 2002;Hinz et al, 2012;Jooyandeh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that MTG enzyme improves the textural properties of low-fat ice cream and increases melting resistancy and stability of it (Metwally, 2007; Rossa et al, 2011;Kafshgari et al, 2014;Kasprzyk et al, 2016). However, there is no study on the use of MTG enzyme as a stabilizer in ice cream production.…”
Section: Introductionmentioning
confidence: 99%